IMPLEMENTASI TOLAK UKUR PEMBERIAN SANKSI REHABILITASI BAGI PECANDU NARKOTIKA DI KOTA PEKANBARU - Sarah Doviola Sipangkar; Zulfikar Jayakusuma; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
With this, it is hoped that Narcotics abusers will be snared in accordance with Article 127 ofLaw Number 35 of 2009 concerning Narcotics, where the judge can decide or stipulate to orderaddicts to undergo Rehabilitation. The main problems in this research are: What are thebenchmarks for giving rehabilitation sanctions for narcotics users based on Law Number 35 of2009 and what are the shortcomings in providing rehabilitation sanctions for narcotics abuse inIndonesia.This type of research can be classified in the type of sociological law, because in this studythe author directly conducts research on the location or place under study in order to provide acomplete and clear picture of the problem under study. This research was conducted in thejurisdiction of the Pekanbaru City National Narcotics Agency. while the population and sample areall parties related to the problems studied in this study, the data sources used are primary data,secondary data, research subjects, related to data collection in this study by observation, interviewsand literature studyThe determination of sanctions on drug abuse and addicts is the absolute right of the judge.Because the provisions of Law Number 35 of 2009 concerning Narcotics explain that judges aregiven the authority to determine and impose imprisonment or rehabilitation measures on narcoticsaddicts. In handling cases of narcotics addicts, the judge applies the provisions of Article 127 ofLaw Number 35 of 2009 concerning Narcotics regarding criminal sanctions and Article 103 of LawNumber 35 of 2009 concerning Narcotics regarding sanctions for rehabilitation. The rulesregarding Narcotics should be regulated strictly in the eradication of narcotics crimes andoverlapping rules should be regulated to be able to complement each other.Keywords: Criminal, Narcotics, Rehabilitation.